Compensatory Mechanism for Face Perception Suggested by a SPECT Activation Study - Kanemura, Hideaki; Mizorogi, Sonoko; Sugita, Kanji; Aihara, Masao (Journal of Pediatric Neurology, 2016)
Background The bilateral temporo-occipital lobes are the usual site of pathology in patients with prosopagnosia. However, the mechanisms leading to this disorder are not fully understood. We investigated the neural mechanism of compensation for prosopagnosia in a patient with focal right posterior temporal lobe encephalitis without prosopagnosia.Methods A single-photon emission computed tomography (SPECT) scan was performed using a brain-dedicated 32-phototube SPECT scanner and technetium-99m hexamethyl-propylene amine oxime to measure regional cerebral blood flow (rCBF). A SPECT activation study was performed in each of two conditions: the familial faces retrieval task and a control task.Results The SPECT activation study revealed a significant increase in rCBF in the contralateral temporal lobe (from 72 during control conditions to 99 mL/100 g/min during the activation paradigm).Conclusions This finding suggests that the region contralateral to the brain lesion compensates for the function of face perception. Our result may explain the reason why prosopagnosia rarely occurs with single, well-circumscribed lesions. The activation pattern seen in this study may be helpful for understanding the neural mechanism of compensation for prosopagnosia.
Keywords: prosopagnosia; face perception; compensation; single-photon emission computed tomography; regional cerebral blood flow